2007
DOI: 10.1029/2006jc003969
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hot event in the equatorial Indo‐Pacific warm pool using advanced satellite sea surface temperature, solar radiation, and wind speed

Abstract: [1] Using advance satellite-derived sea surface temperature (SST), solar radiation and wind speed products, we investigate hot events (HEs) associated with very high SST of around 30°C. Amplitude of the SST diurnal variation (DSST) is obtained by an empirical formula with the downward surface shortwave radiation (DSSR) and the wind speed. The HE is defined as a connected region with SST > the time-dependent SST threshold of about 30°C having a minimum areal size greater than 3 Â 10 6 km 2 and lasting for a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
59
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(62 citation statements)
references
References 25 publications
3
59
0
Order By: Relevance
“…Over the course of 10 years (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003), they identified 31 HEs distributed in the tropical oceans, with most of the HEs (68 %) detected in the western equatorial Pacific. This and subsequent studies concluded that the HEs occur when there are high levels of solar radiation and low wind speeds, and that HE development involves a high diurnal SST amplitude Qin et al 2007Qin et al , 2008Kawamura 2009, 2010). However, there are still some problems with their detection method.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Over the course of 10 years (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003), they identified 31 HEs distributed in the tropical oceans, with most of the HEs (68 %) detected in the western equatorial Pacific. This and subsequent studies concluded that the HEs occur when there are high levels of solar radiation and low wind speeds, and that HE development involves a high diurnal SST amplitude Qin et al 2007Qin et al , 2008Kawamura 2009, 2010). However, there are still some problems with their detection method.…”
Section: Introductionmentioning
confidence: 96%
“…Using this dataset reduced sampling and merging errors. Then we improved the HE detection method proposed by Qin et al (2007) by taking seasonal SST variations into account. The application of this method allowed us to obtain new results on HE climatology in the western equatorial Pacific and to explore the relation of HEs to the western Pacific warm pool, as discussed in this paper.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Detection of very high SST (around 30°C) within the warm pool is associated with the strong intraseasonal variability of hot events (Qin et al 2007). Zonal displacement of the warm pool is also important for the onset of the El Niño Southern Oscillation (ENSO) phenomenon (Picaut et al 1996;Ando and Hasegawa 2009).…”
Section: Introductionmentioning
confidence: 99%